Influence of fish attractant on hooking location of Lutjanus carponotatus and Epinephelus quoyanus caught with soft plastic and hard‐bodied lures. (6th August 2022) - Diggles, Ben K.; Ernst, Ingo; Wesche, Stephen; Scutt, Katie
Abstract: Recreational fishing gear continues to evolve, and factors such as anatomical hooking location may change over time due to technology creep. We revisited studies conducted in 1996 by re‐examining hooking location in experiments where hard‐bodied and soft plastic lures were presented to stripey ( Lutjanus carponotatus ) and wire netting cod ( Epinephelus quoyanus ) either with or without application of a synthetic fish attractant. These data were compared to those of fish hooked on organic bait using circle or J‐style hooks. Lure type and application of attractant both significantly affected hooking location. Addition of attractant to hard‐bodied lures reduced foul hooking of both species. For L. carponotatus, soft plastic lures both with and without attractant tended to be taken deeper than hard‐bodied lures. For E. quoyanus captured on soft plastic lures coated with attractant, hooking locations were similar to those using organic baits on circle hooks. However, deepest hooking of both species occurred using organic bait on J‐style hooks. The use of soft plastic lures with an effective fish attractant may result in deeper hooking, which could potentially influence post‐release survival and increase fishing power.